Comparison Of Rubber Ball Graining Therapy and Constraint Induced Movement Therapy (Cimt) on Improving Muscle Strength in Ischemic Stroke Patients in theWant to be a successful Pukes Center Work Area - Hardi, Anisa Kamilia Putri; putra, Eridha Putra; Rehmaita Malem; Ully Muzakir; Ferdi Riansyah (Teewan Journal Solutions, 2026)
Ischemic stroke is a neurological disorder that frequently causes weakness in the upper extremities, hindering patients' independence in daily activities. According to WHO (2024), 15 million people suffer a stroke annually, and in Indonesia, the prevalence of stroke reaches 10.9% (Riskesdas 2018). This study, conducted in the working area of the Ingin Jaya Community Health Center, Aceh Besar Regency, aimed to compare the effectiveness of rubber ball squeeze therapy and Constraint Induced Movement Therapy (CIMT) in improving upper extremity muscle strength in ischemic stroke patients. The research utilized a Quasy experiment with a two-group pretest-posttest with control group design, involving 32 patients. Based on the normality test results, the data were not normally distributed, so a non-parametric test was used. The study results showed that both types of therapy had a significant effect. The mean muscle strength of the rubber ball squeeze therapy group increased from 2.69 to 4.19, while the CIMT group increased from 2.81 to 4.44. This improvement was proven significant by the Wilcoxon Signed Ranks Test (p < 0.05). However, the Mann-Whitney Test revealed no significant difference between the effectiveness of the two therapies (p = 0.100). Thus, it can be concluded that both rubber ball squeeze therapy and CIMT are effective in improving upper extremity muscle strength, although there is no difference in effectiveness between them. This thesis was completed on May 9, 2025.